Manufacture and Characterization of Good Manufacturing Practice-Compliant SARS-COV-2 Cytotoxic T Lymphocytes. (30th December 2022) - Chu, Yaya; Milner, Jordan; Lamb, Margaret; Maryamchik, Elena; Rigot, Olivia; Ayello, Janet; Harrison, Lauren; Shaw, Rosemarie; Behbehani, Gregory K; Mardis, Elaine R; Miller, Katherine; Prakruthi Rao Venkata, Lakshmi; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 virus-specific cytotoxic T-cell lymphocytes (vCTLs) could provide a promising modality in COVID-19 treatment. We aimed to screen, manufacture, and characterize SARS-CoV-2–vCTLs generated from convalescent COVID-19 donors using the CliniMACS Cytokine Capture System (CCS). Methods: Donor screening was done by stimulation of convalescent COVID-19 donor peripheral blood mononuclear cells with viral peptides and identification of interferonγ (IFN-γ) + CD4 and CD8 T cells using flow cytometry. Clinical-grade SARS-CoV-2–vCTLs were manufactured using the CliniMACS CCS. The enriched SARS-CoV-2–vCTLs were characterized by T-cell receptor sequencing, mass cytometry, and transcriptome analysis. Results: Of the convalescent donor blood samples, 93% passed the screening criteria for clinical manufacture. Three validation runs resulted in enriched T cells that were 79% (standard error of the mean 21%) IFN-γ + T cells. SARS-CoV-2–vCTLs displayed a highly diverse T-cell receptor repertoire with enhancement of both memory CD8 and CD4 T cells, especially in CD8 TEM, CD4 TCM, and CD4 TEMRA cell subsets. SARS-CoV-2–vCTLs were polyfunctional with increased gene expression in T-cell function, interleukin, pathogen defense, and tumor necrosis factor superfamily pathways. Conclusions: Highly functional SARS-CoV-2–vCTLs can be rapidly generated by direct cytokine enrichment (12 hours) from convalescent donors. Clinical Trials Registration: NCT04896606. Abstract : Highly functional SARS-CoV-2–vCTLs can be rapidly generated from convalescent COVID-19 donors using the CliniMACS Cytokine Capture System. SARS-CoV-2–vCTLs displayed a highly diverse TCR repertoire, enhanced memory CD8 and CD4 T cells, and increased gene expression in T-cell function and other pathways.